Diagnostik und Therapie des idiopathischen nephrotischen Syndroms im Kindesalter - Querfeld, Uwe; Tönshoff, Burkhard (Monatsschrift Kinderheilkunde, 2017)
The German Society for Pediatric Nephrology (GPN) has issued a guideline for diagnosis and differential diagnosis of the idiopathic nephrotic syndrome and for therapy of the steroid-sensitive nephrotic syndrome (SSNS) in childhood. Children with SSNS usually remain steroid sensitive and have in general a good prognosis even with frequent relapses. Initial manifestations and relapses should be treated with standard steroid therapy according to the current recommendations. Up to 80-90% of patients with SSNS experience relapses, either in the form of infrequent relapses (about 30%) or frequent relapses with or without steroid dependency (30-50%), and up to 15% of patients may become steroid resistant during follow-up. There is a high risk for steroid toxicity in patients with frequent relapses, which increases with duration of therapy and cumulative steroid exposure. Patients with steroid-induced side effects should therefore be treated with steroid-sparing medications. Therapeutic options include cyclosporin A, tacrolimus, mycophenolate mofetil, cyclophosphamide, levamisol, and rituximab. Patients with frequent relapses, steroid-dependent or steroid-resistant NS should be referred to specialized centers for pediatric nephrology. All medications may have serious side effects and complications. Treatment of these patients is demanding and often requires follow-up and immunosuppressive and supportive therapy over many years to prevent long-lasting damage to health.
Online publiziert: 20. Juni 2017
Gesehen am 22.10.2018